Program Baca Tulis Qur’an Dasar Mahir Berbahasa Arab - Nurul Hariani; Santi Juliana Silalahi; Widya Indah Rengganis (Maslahah: Jurnal Pengabdian Masyarakat, 2020)
To be proficient in Arabic, surely we must do it on the basis to train and get used to it. As based on the introduction of the Separate Arabic Letters, the Hijaiyah Letters, which consist of 28-30 Letters. In updating Arabic language by recognizing Hijaiyah letters there must be special learning that must be achieved, for example Special learning to recognize Hijaiyah Letters begins with reading Beginner's Iqro Book, starting from Iqra '1 to 6. Furthermore, to be proficient in writing also basically is to recognize letters and get special learning. So to achieve this we can do beginner learning to be proficient in Arabic, starting from reading, translating and writing to that is by taking the class of Reading the Qur'an (BTQ). There we can make beginners, write, read, to translate it, and also recognize the Law of reading (Tajweed). Anyone To be proficient in Arabic and the writing must go through the basics first. Whether it's children to adults though.Keyword: Learning , Read The Qur’an, Arabic